High‐Pressure Synthesis of a Nitrogen‐Rich Inclusion Compound ReN8⋅x N2 with Conjugated Polymeric Nitrogen Chains. (19th June 2018) - Bykov, Maxim; Bykova, Elena; Koemets, Egor; Fedotenko, Timofey; Aprilis, Georgios; Glazyrin, Konstantin; Liermann, Hanns‐Peter; Ponomareva, Alena V.; Tidholm, Johan; Tasnádi, Ferenc; Abrikosov, Igor A.; Dubrovinskaia, Natalia; et al.
Abstract: A nitrogen‐rich compound, ReN8 ⋅x N2, was synthesized by a direct reaction between rhenium and nitrogen at high pressure and high temperature in a laser‐heated diamond anvil cell. Single‐crystal X‐ray diffraction revealed that the crystal structure, which is based on the ReN8 framework, has rectangular‐shaped channels that accommodate nitrogen molecules. Thus, despite a very high synthesis pressure, exceeding 100 GPa, ReN8 ⋅x N2 is an inclusion compound. The amount of trapped nitrogen (x) depends on the synthesis conditions. The polydiazenediyl chains [−N=N−]∞ that constitute the framework have not been previously observed in any compound. Ab initio calculations on ReN8 ⋅x N2 provide strong support for the experimental results and conclusions.